Understanding the Influence of Orphanages on Children's Social Attitudes within Institutional Care Settings - Nathanael, Christian; Arshaka, Muhammad Arshaka; Azahra, Salsabilla Azahra (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2023)
This study delves into the intricate dynamics within orphanages to illuminate their impact on children's social attitudes within the Sidikalang Children's Social Services UPT. Through a mixed-methods approach integrating surveys, interviews, and observations, the research explores the multifaceted influences shaping social attitudes among children residing in institutional care. Findings unveil the pivotal role of caregiver-child relationships, emphasizing the significance of positive, consistent interactions in fostering trust, empathy, and healthy social behaviors. Moreover, insights into the interplay between institutional environments, peer dynamics, and children's transition to society underscore the complexities and nuances shaping social attitudes within orphanages. Implications emanating from these findings advocate for caregiver training programs, child-centric care environments, and interventions fostering positive peer relationships. While acknowledging limitations in sample representativeness and data collection subjectivity, this research charts pathways for future endeavors highlighting the need for holistic, nurturing environments within institutional care settings. Ultimately, the study beckons for transformative approaches that nurture resilience, empathy, and positive social attitudes among children growing up in institutional care.